Distinct patterns of respiratory difficulty in young children with achondroplasia: a clinical, sleep, and lung function study. Issue 2 (1st August 1998) - Tasker, Robert C; Dundas, Isobel; Laverty, Aidan; Fletcher, Margaret; Lane, Roderick; Stocks, Janet
Abstract : AIM: Achondroplasia can result in respiratory difficulty in early infancy. The aim of this study was to document lung growth during infancy, together with the cause of any cardiorespiratory and sleep dysfunction. PATIENTS AND METHODS: Seventeen prospectively ascertained infants (14 boys and three girls) with respiratory symptoms starting before 1 year of age underwent clinical, sleep, and lung function studies. RESULTS: Three distinct groups were identified. Group 1 (n = 6) were the least symptomatic and only had obstructive sleep apnoea. Group 2 (n = 6) had obstructive sleep apnoea of muscular aetiology and, neurologically, hydrocephalus and a small foramen magnum were common. Group 3 (n = 5), the most severely affected group, all developed cor pulmonale, with three deaths occurring as a result of terminal cardiorespiratory failure. All five had obstructive sleep apnoea with a muscular aetiology (a small foramen magnum predominated) with severe or moderately severe gastro-oesophageal reflux. Initially, lung function studies found no evidence of restriction or reduced lung volumes standardised according to weight. However, with growth these infants had worsening function, with raised airway resistance and severe reductions in respiratory compliance. CONCLUSIONS: These groups appear to be distinct phenotypes with distinct anatomical aetiologies: "relative" adenotonsillar hypertrophy, resulting from a degree of midfacial hypoplasia (group 1); muscular upper airway obstruction along with progressive hydrocephalus, resulting from jugular foramen stenosis (group 2); and muscular upper airway obstruction, but without hydrocephalus, resulting from hypoglossal canal stenosis with or without foramen magnum compression and no jugular foramen stenosis (group 3). The aetiology of these abnormalities is consistent with localised alteration of chondrocranial development: rostral, intermediary and caudal in groups 1, 2, and 3, respectively.